2020
DOI: 10.1097/j.pain.0000000000002038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex on placebo effects in chronic pain participants: a cross-sectional study

Abstract: Sex-related differences can influence outcomes of randomized clinical trials and may jeopardize the effectiveness of pain management and other therapeutics. Thus, it is essential to understand the mechanistic and translational aspects of sex differences in placebo outcomes. Recently, studies in healthy participants have shed light on how sex-related placebo effects might influence outcomes, yet no research has been conducted in a patient population. Herein, we used a tripartite approach to evaluate the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Alongside the promise of QST in improving the characterization of pain, and in turn, the prescription of individualized treatment interventions, limitations of this methodology must also be addressed. As highlighted in our descriptions of QST in TMD and placebo research, sex and racial effects regarding pain sensitivity, and racial effects regarding placebo efficiency have been observed, and thus need be accounted for when analyzing results ( 57 , 58 ). In addition, effects of age must be considered when incorporating QST, as loss of sensory function has been observed in older adults for cold, warmth, mechanical, and vibratory detection thresholds ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside the promise of QST in improving the characterization of pain, and in turn, the prescription of individualized treatment interventions, limitations of this methodology must also be addressed. As highlighted in our descriptions of QST in TMD and placebo research, sex and racial effects regarding pain sensitivity, and racial effects regarding placebo efficiency have been observed, and thus need be accounted for when analyzing results ( 57 , 58 ). In addition, effects of age must be considered when incorporating QST, as loss of sensory function has been observed in older adults for cold, warmth, mechanical, and vibratory detection thresholds ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that Afro-American Blacks had lower pain tolerance in both TMD participants and healthy control participants ( 57 ). Additionally, we found women in the TMD cohort to have lower levels of both thermal heat pain threshold and thermal heat pain tolerance than men ( 58 ). Both results are in line with the literature on racial and sex effects with regard to pain sensitivity, as in experimental pain studies, women tend to be more sensitive to pain than men in measures of heat, cold, and pressure pain tolerance ( 55 , 59 , 60 ).…”
Section: Temporomandibular Disordersmentioning
confidence: 96%
“…Sex and race matter for placebo effects. Females and white populations seem to experience larger placebo effects [ 114 , 115 ]. Another set of important predictors of placebo effects is psychological factors, e.g., expectation, trait optimism, desire for control [ 116 ], emotional distress, and maladaptive cognitive appraisals of pain [ 117 ].…”
Section: Translating Basic Research Findings Into Clinical Treatment ...mentioning
confidence: 99%
“…Recently, Enck and Klosterhalfen (2019) showed that males are more responsive to verbally generated placebo treatments, while females are more responsive to placebo treatments generated by classical conditioning. However, the inconsistent findings (e.g., females also have been shown to be more responsive to verbally produced placebo effects; Olson et al, 2021 ), and the interaction of participant and experimenter/clinician sex (e.g., Mogil, 2012 ), have made it difficult to understand the effects of sex/gender on placebo effects.…”
Section: Introductionmentioning
confidence: 99%